Nowoczesne technologie a uczniowie z dysleksją – możliwości i zagrożenia - PAWLUK-SKRZYPEK, AGNIESZKA; BŁASZCZAK, IWONA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Agnieszka Pawluk-Skrzypek, Iwona Błaszczak, Nowoczesne technologie a uczniowie z dysleksją – możliwości i zagrożenia [Modern technologies and students with dyslexia – opportunities and threats]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 235-247. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.14 The article focuses on the issue of the possibility of using modern technologies in the education and pedagogical therapy of students with developmental dyslexia. The article draws attention to the difficulties experienced by students with developmental dyslexia in contact with modern technologies due to the specificity of their functioning, which consists in the fact that their problems “do not manifest themselves only within the letter system, but apply to all character systems (symbols), which exist to denote (naming, ordering) the existing reality. This also applies to codes that regulate the use of certain symbols, in other words – dyslexia causes difficulties with the use of symbols and the abstraction and application of rules for the use of these symbols. Both letters and numbers, notes, Morse code, numeric time stamping, etc”.